East Java Economic Model: Monetary Policy Implications in the Middle of the Covid-19 Crisis - Ahmad Zainuddin; Julita Hasanah (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2020)
East Java is the epicenter of Covid-19 with the highest number of positive cases in Indonesia (11,508 cases as of June 28th, 2020) surpassing DKI Jakarta. The massive spread of the virus had economic consequences. Data showed that East Java's regional income in the third quarter of this year grew negatively by 5.90% (yoy). The contraction of East Java's economic growth will affect the national economy, known that East Java was the second largest contributors to national income, with a contribution of 14.61% in 2017 (Bank_Indonesia, 2018). East Java's economic problems as a result of the pandemic need to involve a comprehensive analysis in order to produce suitable policy implications. The purpose of this study is to predict the development of the Covid-19 case in East Java, to analyze the impact of Covid-19 on the East Java economy including economic growth, inflation, exchange rates, household and government consumption as well as effective macro policy simulations as a novelty of research. This research used descriptive analytical method by involving various simulations. Based onthe results of the study, it is known that (1) the increase in Covid-19 (2.5 times) without any government policy has an impact on the decrease in East Java's regional income by 1.31% or equivalent to 4655 billion Rupiah/quarter, (2) Increasing the number The spread of covid-19 by 2.5 times accompanied by the provision of consumption credit and agricultural credit of 5% will have an impact on increasing East Java's regional income by 0.57% or equivalent to Rp. 2,021 billion/quarter, (3) An increase in consumption credit by 15% means an increase in household consumption. 2.72% or equivalent to Rp. 5,985 billion/quarter, and (4) The policy to increase money supply by 15% has an impact on increasing public consumption by 0.69% or equivalent to Rp. 1,521 billion/quarter. Based on the results, it can be concluded that the most effective policy in order to reduce the economic impact of Covid-19 is the policy to increase the provision of credit to the public in the form of consumption credit or agricultural credit by 15%.